Safety Calculation and Testing of Falling Protector based on Passive Technology - Han Yukun; Li Junmin; Zhang Yunzhen; Lü Guobin (Jixie chuandong)
The anti-falling safety is one of the key techniques for attached lifting scaffold. Aiming at the design defects of other structural style falling protectors,the structural features and working principle of star wheel falling protector based on passive technology are analyzed. The strength of critical parts in falling protector are checked by the strength calculation method of ratchet wheel. The calculation results show that the strength of inner ratchets and wedge block meet the requirements. By the anti-falling performance testing of scaffold,the results show,every falling protector can brake instantly to prevent continued falling when the scaffold falls. The falling distance of four position less than the specified value in national standards. The falling protector can effectively brake,which is safe and has a wide popularization and application prospect.